SERTIFIKAT BUKAN HAK MUTLAK DALAM KEPEMILIKAN TANAH Kajian Putusan No.1333/Pdt.G/2021/PN.Tng - Tikara, Daniel Calvin; Murary, Weron; Morinto, Reymond (Ensiklopedia of Journal, 2024)
Abstract: Criminal laws are legislation that regulates deeds that can be punished or punished. In chapters 338 and 340 are arranged regarding the act of loss of the life of another person resulting in a accountable or render a criminal. The problem in this study refers to the planned murder crimes that occurred in the kisor maybrat reside at the tni kisor post that is contained in the sorong state court ruling 208/ pid. B/2023. In this case there was a problem with a trial of obstructions involving a person involved in the proceedings. Therefore the writer would like to address the matter of evidential proceedings in the trial of the accused in order to prove the prosecution's allegations to be true from the premeditated elements of the murder of the prosecutor, and the court's decision to pass a sentence on the defendant in the role of the accused of the crimes of premeditated murder. This research approach USES normative-empirical jurisdiction. The data sources used are found in the primary and secondary data. Data collecting USES literature studies and field studies. The data analysis used USES qualitative prescriptive data analysis. The results of this study are evidence in the trial obtained the fact that the accused was indeed a person involved in the planning and execution of the tni kisor maybrat post murder and assault based on the evidence available in the form of witness testimony, letters and instructions of a surveillance video of the accused in the police force. Witnesses easement the accused and his associates' statements with the defendant could not prove their innocence, as well as the verdict given by the judge according to the prosecution's claim by taking into account the role of the accused in this case and the attitude of the accused during the trial, the verdict was that of a 20-year prison sentence, in contrast with the defendant's being sentenced only to life imprisonment because the defendant was only on duty in front of the tni post.Keywords: Evidence. Judgment, Premeditated Murder.